Effect of Eco-Degradant on Properties of Recycled Polyethylene (RPE)/Chitosan Biocomposites - Husseinsyah, Salmah; Nurain, Azieyanti; Suppiah, Kathiravan (Penerbit Universiti Sains Malaysia, 2016)
The effect of eco-degradant PD 04 on properties of recycled polyethylene (RPE)/chitosan biocomposites was investigated. RPE/chitosan biocomposites were prepared by using Z-blade mixer at processing temperature 180°C and rotor speed 50 rpm. Eco-degradant PD 04 was used as degradant additive to improve the properties of biocomposites. The result indicated that the increasing of filler loading increased tensile strength, Young's modulus and water absorption but reduce the elongation at break. The presence of eco-degradant showed that the tensile strength and Young's modulus were increased but reduce the elongation at break. The water absorption of biocomposites with eco-degradant PD 04 has better water resistance compared to biocomposites without eco-degradant PD 04